If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 100 + 8h = 10h Solving 100 + 8h = 10h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-10h' to each side of the equation. 100 + 8h + -10h = 10h + -10h Combine like terms: 8h + -10h = -2h 100 + -2h = 10h + -10h Combine like terms: 10h + -10h = 0 100 + -2h = 0 Add '-100' to each side of the equation. 100 + -100 + -2h = 0 + -100 Combine like terms: 100 + -100 = 0 0 + -2h = 0 + -100 -2h = 0 + -100 Combine like terms: 0 + -100 = -100 -2h = -100 Divide each side by '-2'. h = 50 Simplifying h = 50
| -3(t-2)+8t=7t-1 | | 5x^4-24x^2+16=0 | | 1/4(x+2)=-6 | | 9(y-8)/2=-2y | | 4+12p-1=8p+13-6p | | 5(4x+5)+4=20x+29 | | 10.00+3x=46 | | -1/5(x+1)=-8 | | 1/4(x+2)=11 | | 1/5(x+1)=-10 | | 0.04(y-1)+0.02y=0.16y-0.03(30) | | 3y-2.72y=9 | | 3v+(-8.8)=188.0 | | -1/5(x+4)=-9 | | a^2-18a+81= | | 6y+1/5=7y+7/5 | | 53=86/z | | (1+x)3-x=17 | | V+(v-32.6)+(v+23.8)=188.0 | | 13/6x=39 | | 110x-x^2-1000=0 | | -3(2x+2)=12 | | 5(x+4)+4=19 | | C(x)=8x+15 | | -2(3x+2)= | | C(x)=8+15 | | R(x)=52x-0.3x^2 | | (x+3)6=10x | | 3(x-2)-x=0 | | x+12=62 | | 1(x-3)=-4 | | -2x+2(2)=14 |